THE POLYMORPHISM OF THE SUS4 SUCROSE SYNTHASE DOMAIN SEQUENCES IN RUSSIAN, BELORUSSIAN AND KAZAKH POTATO CULTIVARS - M. A. Slugina; T. I. Zapekina; A. A. Meleshin (Овощи России)
The potato is one of the main strategic crops in the Russian Federation, Belarus and Kazakhstan. Currently, we have achieved significant advances in the understanding of metabolic mechanism of carbohydrate and interconversion «sucrose – starch» in potato tubers. Sucrose synthase (Sus) is a key enzyme in the breakdown of sucrose. Sucrose synthase (Sus) is catalyzing a reversible reaction of conversion sucrose and UDP into fructose and UDP-glucose. The identification and subsequent characterization of the genes encoding plant sucrose synthase is the first step towards understanding their physiological roles and metabolic mechanism involved in carbohydrate accumulation in potato tubers. In the present work the nucleotide and amino acid polymorphism of the Sus4 gene fragments containing sequences of the sucrose synthase domain were analyzed. Sus4 gene fragments (intron III – exon VI) in 9 potato cultivars of Russian, Kazakh and Belarusian breeding were analyzed. The polymorphism of the Sus4 sucrose synthase domain sequences was first examined. The length of analyzed fragment varied from 977 b.p. (cultivars Favorit, Karasaiskii, Miras) to 1013 b.p. (cultivars Zorochka, Manifest, Elisaveta, Bashkirskii). It was demonstrated that the examined sequences contained point mutations, as well as insertions and deletions. The common polymorphism level was 5.82%. It was shown that the examined sequences contained 58 SNPs and 4 indels. The most variable were introns IV (12.4%) and V (9.18%). The most variable was exon IV. 7 allelic variants were detected. 6 different amino acid sequences specific to different varieties were also identified.